Psychological Features of Adolescence - Boltaboyev Azizbek Xasanboy o’g’li; Ahmedov Davlatbek Saloxiddin o’g’li (Genius Journals, 2022)
The article discusses adolescence and its specific features, and the physical, spiritual and anatomical changes that occur in the adolescent psych. It also provides an analysis of their psychological characteristics, which are characteristic of cognitive processes.
Keywords: Adolescence; worldview; deviant; acceleration